IMPROVEMENT OF ECOLOGICAL STATUS OF SOIL IN ORGANIC AGRICULTURE - Elmuradova Matluba (International Engineering Journal For Research & Development, 2020)
This article investigates major points of this improvement of ecological status of soil in organic agriculture. Moreover, on this way, soil in organic agriculture has been investigated both theoricatal and methodological ways. Finally, research has been pinpointed on various categories to make further developments.